A Mixed Methods Investigation of Stress and Wellbeing Factors Contributing to Burnout and Job Satisfaction in a Specialist Small Animal Hospital - Ashton-James, Claire E.; McNeilage, Amy G. (Frontiers in Veterinary Science, 2022)
Occupational burnout is a critical issue affecting the welfare of veterinary care providers, their patients, and the sustainability of veterinary healthcare organizations. The current research aimed to evaluate the prevalence of and factors contributing to stress, wellbeing, burnout symptoms and job satisfaction among clinical and non-clinical staff at a large specialist small animal hospital in Australia. Participants completed an anonymous online survey including self-report measures of job satisfaction and symptoms of burnout, and open-text response questions probing sources of stress and wellbeing. Subsequently, participants rated how frequently they experienced commonly reported sources of veterinary stress, and a series of focus groups were conducted with clinical and non-clinical teams. The survey was completed by 249 participants (overall response rate = 70%; 67.1% “clinical;” 17.3% “non-clinical;” 5.6% “other”). Five focus groups (including 38 of the survey participants) were subsequently conducted with groups of clinical and non-clinical staff. The majority of respondents (80.7%) reported being satisfied, very satisfied, or extremely satisfied with their job. At the same time, 57.7% of respondents exceeded the threshold for burnout on at least one burnout dimension, with 48.1% reporting high levels of emotional exhaustion, 30.2% reported high levels of cynicism, and 16.3% reporting low levels of professional efficacy. Open text responses and focus group transcripts revealed three common sources of stress and wellbeing. Stressors included communication (conflict within teams), clients (dealing with client emotions and expectations), and heavy caseload. Wellbeing was enhanced by people (team cohesion, respect for colleagues), practice (variety, autonomy, challenge), and purpose (meaningful work and impact). Overall, for both clinical and non-clinical survey respondents, “heavy workload” was rated as the most frequent source of stress. Despite high levels of job satisfaction, approximately two thirds of respondents reported at least one symptom of burnout. Convergent results from the survey and focus groups indicated that strong relationships with colleagues and the intrinsic meaningfulness of the work were key sources of wellbeing and job satisfaction. On the other hand, challenging workplace interactions with colleagues and clients, as well as heavy workload, were identified as key stressors contributing to burnout symptoms.